(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
High-rise construction volume increase and new wall materials use require changing the approach to the design of plaster mortar compositions. The analysis has showed that it is possible to reduce the number of cracks in the plaster coating by increasing the water holding capacity of the mortar mixture. To optimize the prescription parameters of the mortar mixture, the five-factor experiment with fine aggregate and the filler with a low modulus of elasticity, disperse polymeric powders and cellulose ethers, a polymer fiber for microdispersed reinforcement has been used. The obtained data indicate that the proposed approach enables to obtain plaster mortars with physic mechanical characteristics that provide optimal working conditions “masonry - plaster coatings”.